Perancangan dan Implementasi Sistem Informasi Marketplace Danzu Store dari Sisi User - Akhmad Sayuti; M. Irdan Aljibran; Bella Paramita (Journal Of Software Engineering And Communication, 2026)
The development of information technology is driving digital transformation in the trade sector, particularly in the marketplace business model. Danzu , as an online sales-based business unit, faces challenges in providing effective, efficient, and user-friendly services to customers. This study aims to design and implement a Danzu  marketplace information system that focuses on User Experience and needs (user-oriented system). The system development method used is the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and Maintenance. In the analysis stage, functional and non-functional needs are identified from the user's perspective, such as registration and login features, product search, shopping cart, checkout process, payment confirmation, order tracking, and user profile management. The system design was carried out using the Unified Modeling Language (UML) which includes use case diagrams, activity diagrams, and sequence diagrams to model the interaction between users and the system. The system implementation was carried out using web-based technology with a programming language that supports dynamic application development and a database for managing product, transaction, and user data. The resulting system is able to facilitate users in conducting online transactions, increase the speed of access to product information, and provide a more structured and transparent shopping experience. Test results show that the Danzu  marketplace system runs according to user needs, has a responsive interface, and is able to increase the efficiency of the transaction process compared to the previous system which was still manual or semi-digital. Thus, this system is expected to support increased customer satisfaction and the competitiveness of the Danzu  business in the digital era.